Does Foreign Direct Investment Improve Innovation in Domestic Firms? An Empirical study on FDI spillovers and their impact on a Country and Regional-Level in China, 2011-2014. - Wilson, J. L. (2016)
This thesis examines the relationship between FDI spillovers and innovation at both a country and provincial level China in the period 2011-2014. This paper finds that positive spillovers occur at a country level, but there is variance in the effects of FDI spillovers between provinces. Spatial proximity of local firms to FDI and the effects of different types of FDI are examined and we find evidence of demonstration effects and labour turnovers taking place. This paper adds to existing spillover literature by illustrating how regional variation, geographic proximity and a firms absorptive capacity affect the magnitude of spillovers. The empirical findings by this paper calls into question the widely accepted view propounded by economic bodies that countries should make policy based concessions to foreign investors because FDI leads to overwhelmingly positive spillovers.